2018
DOI: 10.1038/s41598-018-29774-z
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Weight Gain per Pre-Pregnancy Body Mass Index and Birth Weight in Twin Pregnancies: A Cohort Study in Wuhan, China

Abstract: To assess the relationship between gestational weight gain (GWG) of twin-pregnancy women and twin birth weights, as well as to evaluate whether pre-pregnancy body mass index (BMI) influences this relationship. A cohort study was conducted in Wuhan, China, between 1/01/2011 and 8/31/2017. Women with twin pregnancies who delivered live and non-malformed twins were included (6,925 women and 13,850 infants), based on the Wuhan Maternal and Child Health Management Information System. Logistic regression models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 32 publications
7
41
5
Order By: Relevance
“…Alternatively, the lack of significant association could be partly attributed to the smaller number of women gaining weight inadequately than other groups. Large studies suggested that GWG below the IOM recommendations was associated with an increased risk of SGA twins [27, 29]. On the opposite, we found that weight gain above the recommended GWG was associated with a higher risk of LGA, which is consistent with the previous finding of Ozcan et al [27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Alternatively, the lack of significant association could be partly attributed to the smaller number of women gaining weight inadequately than other groups. Large studies suggested that GWG below the IOM recommendations was associated with an increased risk of SGA twins [27, 29]. On the opposite, we found that weight gain above the recommended GWG was associated with a higher risk of LGA, which is consistent with the previous finding of Ozcan et al [27].…”
Section: Discussionsupporting
confidence: 92%
“…A few of previous studies evaluated the association between maternal weight gain and birth weight without including the length of gestation or chorionicity as confounders [20, 21, 2729]. We thought that these variables play significant roles in fetal growth among twins thus we adjusted these confounders for neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the neonatal outcomes, when compared to the normal reference population, neonates who were born to women with inadequate GWG had a higher risk of being SGA, and those born to women with excessive GWG had a higher risk of being LGA. Previous studies have already reported an association between inadequate GWG and neonates who are SGA, and excessive GWG and neonates who are LGA [32][33][34][35]. Li et al [32] analyzed the data from 33,973 pregnancies in the Chinese population and reported that the aORs for LGA infants with excessive GWG and SGA infants with inadequate GWG were 2.32 and 1.41, respectively (95% CI, 2.12-2.53 and 1.26-1.57, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, our study provided reliable results through multivariate analysis of factors such as maternal outcomes through binary logistic regression and neonatal outcomes by the GEE. Although the gestational age at birth, chorionicity, and fetal sex are important variables that can lead to adverse outcomes, many previous studies did not correct for them [34,[36][37][38][39]. In addition, GEE analysis, which is a method used to adjust for the correlation between twins, was not performed in previous studies despite its necessity [22,34,36,39].…”
Section: Discussionmentioning
confidence: 99%
“…These guidelines reflect the 25th and 75th percentile range of total weight gain among women who delivered twins weighing ≥2500 g on average at 37-42 weeks gestation. Women with GWG below the IOM guidelines for twin pregnancies are at increased risk for preterm delivery [8][9][10] and small for gestational age infants [10][11][12][13][14], while GWG within or above guidelines is associated with normal birth weight [9,12,15,16]. Limited evidence also suggests that women with weight gain above guidelines during twin pregnancies are at higher risk for maternal complications, including gestational diabetes, pregnancyinduced hypertension, preeclampsia, or anemia (aOR 1.63, 95% CI: 1.02-2.60) and cesarean delivery (aOR 1.85, 95% CI: 1.20-2.87) [17].…”
Section: Introductionmentioning
confidence: 99%